Penggunaan Tata Bahasa Netizen Dikolom Komentar Instragram Yang Membicarakan Tentang Pemilu 2024 - Siti Aisyah; Ferdy Briliant Oktaviano; Nensy Megawati Simanjuntak (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Abstract  This study aims to investigate the use of netizen grammar in the Instagram comment section discussing the 2024 Election issue, with a focus on language style, conversational patterns, and their impact on public opinion and the democratic process. Employing a qualitative approach, data for this research were collected through direct observation of netizen comments on Instagram. When netizens engage in communication about political issues like the 2024 Election, the grammar they use plays a crucial role in shaping how messages are conveyed and received. This study highlights several common grammar mistakes that may occur, such as spelling errors, improper punctuation usage, and the use of impolite language. For instance, the use of "hati2" instead of "hati-hati" and inconsistent capitalization in "Pak" when used in a context of respect. Analyzing these grammar errors not only aids in understanding how netizens communicate online but also demonstrates their potential impact on public opinion. For example, grammar mistakes can diminish the quality of the message conveyed and influence how it is perceived by readers. Through specific examples, such as errors in sentences expressing prayers for a candidate, this study illustrates how grammar mistakes can reduce communication effectiveness and lower the quality of online discussions. Furthermore, the research underscores the importance of consistency in using formal language in political contexts. Formal language not only reflects politeness in communication but also strengthens public trust in the messages conveyed. Therefore, by improving understanding and practice of correct grammar, it is hoped that online political discussions can become more productive, meaningful, and constructive. The benefits of this research also extend to identifying grammar errors that can affect perceptions of political figures or issues discussed in the context of the 2024 Election. By gaining a better understanding of the dynamics of political communication on social media, it is also possible to enhance public participation in the democratic process. Overall, this study seeks to provide insights into how netizen grammar in Instagram comment sections can influence interactions and public opinions on sensitive political issues. Thus, this research is relevant not only to academics in linguistics and communication but also to political practitioners and the general public seeking a deeper understanding of social media's role in shaping political perceptions and participation.